2016
DOI: 10.1186/s40814-016-0083-x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural activation written self-help to improve mood, wellbeing and quality of life in people with dementia supported by informal carers (PROMOTE): a study protocol for a single-arm feasibility study

Abstract: BackgroundIncreases in life expectancy have resulted in a global rise in dementia prevalence. Dementia is associated with poor wellbeing, low quality of life and increased incidence of mental health difficulties such as low mood or depression. However, currently, there is limited access to evidence-based psychological interventions for people with dementia experiencing low mood and poor wellbeing. Behavioural activation-based self-help, supported by informal carers and guided by mental health professionals, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 88 publications
0
7
0
Order By: Relevance
“…Parents were asked a closed, multiple-choice question regarding reasons for non-participation, reasons were informed by previous research,42 43 and parents could select all applicable reasons: (1) lack of time; (2) physical health; (3) not wanting to participate in research; (4) not liking to talk about personal problems; (5) too tired; (6) not interested in internet-administered self-help; (7) no need for psychological support; (8) child’s health condition and (9) child has recently passed away. The open question at the end of the reasons for non-participation questionnaire was: ‘If you do not want to participate in the project for reasons other than those mentioned above, please write these below’.…”
Section: Discussionmentioning
confidence: 99%
“…Parents were asked a closed, multiple-choice question regarding reasons for non-participation, reasons were informed by previous research,42 43 and parents could select all applicable reasons: (1) lack of time; (2) physical health; (3) not wanting to participate in research; (4) not liking to talk about personal problems; (5) too tired; (6) not interested in internet-administered self-help; (7) no need for psychological support; (8) child’s health condition and (9) child has recently passed away. The open question at the end of the reasons for non-participation questionnaire was: ‘If you do not want to participate in the project for reasons other than those mentioned above, please write these below’.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, reduced resource use suggested potential cost-effectiveness. 50 The transferability of BA to hard-to-reach populations, such as those with aphasia and severe cognitive problems, [51][52][53][54] adds to its potential as a psychological intervention for depression after stroke. Given that the CALM trial 17 demonstrated that it was possible to deliver BA to stroke survivors with aphasia and that studies of BA in people with dementia indicate that it is suitable for those with cognitive impairment, 54 there is significant potential for using BA for treating depression in stroke survivors with mild to moderate communication and cognitive impairment.…”
Section: Behavioural Activationmentioning
confidence: 99%
“…Indeed, a review of interventions for informal caregivers of stroke survivors recommended telephone or internet-administered support to increase access for this population (Bakas et al, 2014). However, evidence indicates that adapting LICBT interventions to represent the needs of specific populations is required to improve acceptability and engagement with adaptations made to interventions for Armed Forces veterans (Farrand et al, 2019), people with dementia (Farrand et al, 2016) and parents of children treated for cancer (Wikman et al, 2018). Failing to adapt LICBT interventions for specific populations may also account for smaller effect sizes experienced by people with chronic health conditions compared with an adult mental health population (Beatty and Lambert, 2013;Farrand and Woodford, 2015), whereas tailoring psychological interventions for informal caregivers resulted in interventions being more effective than non-tailored interventions (Bakas et al, 2014).…”
Section: Introductionmentioning
confidence: 99%